Glutathione sebagai pemutih kulit - Vira Katya Aurelia (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2019)
GSH is one of the compounds that inhibits melanin production by inhibiting tyrosinase activity. Antimelanogenic properties of glutathione have resulted in doctors often giving it as a